Yield Maximization in Pigeonpea through Various Crop Management Practices in Humid South Eastern Plain Zone of Rajasthan - Meena, S. N.; Jadon, Chaman; Meena, B. S.; Meena, H. P.; Singh, Pratap; Jat, M. L. (International Journal of Bio-resource and Stress Management, 2020)
A field experiment was conducted during kharif 2014-15 to 2016-17 at ARS, Kota (Rajasthan) to maximizing the yield of pigeonpea through various crop management practices in humid south eastern plain zone. The experiment was laid out in RBD comprising eight treatments viz., INM (FYM @ 5 t ha-1+RDF i.e. NPKSZn+seed treatment with sodium molybdate @ 4 g kg-1 seed), IWM (Pendimethalin 0.75 kg ha-1 at 3 DAS+Imazethapyr @ 100 g ha-1 at 10-15 DAE of weeds+1 HW/1 inter cultivation at 50 DAS ), IPM (Indoxacarb 15.8% EC at the time of flowering @ 375 ml ha-1+one systemic insecticide spray 15 days after 1st spray), INM+IWM, INM+IPM, IWM+IPM, INM+IWM+IPM and Control (Farmer’s practice) with three replication. On pooled data basis, the result showed that the significant reduction in weed count (No/m2) and dry weight (g/m2) were recorded under INM+IWM+IPM crop management practices, which was statically at par with INM+IWM and IWM+IPM crop management practices. Further results revealed that the significant increase in plant height, yield attributes, grain (1643 kg ha-1), stalk (2720 kg ha-1) and biological yield (4337 kg ha-1) of pigeonpea were obtained and net return (` 5219 ha-1) with B:C ratio (2.10) were fetched under INM+IWM+IPM crop management practices, respectively, as compared to the farmers practices, which was found statistically at par with INM+IWM and IWM+IPM crop management practices.